Dose Dependent Treatment with Boric Acid Induces More Changes in the Sperm Cells of Endangered Anatolian Trout Salmo Rizeensis - Filiz Kutluyerand Mehmet Kocabaş (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2017)
The aim of this study was to test the usefulness of boric acid for endangered Anatolian trout Salmorizeensis sperm. Activation media was supplemented with boric acid (0.5, 1, 2, 3, 4 and 5 mM). Sperm motility and duration were determined in sperm samples. In addition, fertility and hatching rate were examined. Our data indicated that addition of boric acid (3 mM) to activation media was increased the percentage and duration of motile sperm, fertility and hatching rate in endangered Anatolian trout (S. rizeensis). On the other hand, the motility rate decreased with increasing the concentration of boric acid (p<0.05). In particular, a remarkable increase was observed after concentration 3 mM. Consequently, sperm quality was affected by quantitative changes different concentrations of boric acid and the best results were obtained at concentration 3 mM.